1998
DOI: 10.4141/s97-061
|View full text |Cite
|
Sign up to set email alerts
|

Unsaturated hydraulic conductivity of conventional and conservation tillage soils in southern Alberta

Abstract: . Unsaturated hydraulic conductivity of conventional and conservation tillage soils in southern Alberta. Can. J. Soil Sci. 78: 643-648. Conservation tillage is increasing on the Canadian prairies and its long-term effect on soil physical properties warrants investigation. Tension infiltrometer measurements were conducted on conventional tillage (CT), minimum tillage (MT) and no-till (NT) loam to clay loam soils in southern Alberta to determine if 26 yr of conservation tillage (MT, NT) modified the unsaturated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 22 publications
0
13
1
Order By: Relevance
“…For example, some researchers have found no tillage effect (Hill et al 1985;Benjamin 1993) on the soil water characteristic, while others found that NT retained more soil water than CT ( Reynolds et al 1995;Miller et al 1998). Most researchers have found a significant tillage effect on poresize distribution as derived from the soil water characteristic, but they found it was dependent on pore-size (Hill et al 1985), depth (Hermawan and Cameron 1993), soil type (Hill 1990), time of sampling (Carter 1988) and crop rotation (Benjamin 1993).…”
Section: Canadian Journal Of Soil Sciencementioning
confidence: 99%
See 2 more Smart Citations
“…For example, some researchers have found no tillage effect (Hill et al 1985;Benjamin 1993) on the soil water characteristic, while others found that NT retained more soil water than CT ( Reynolds et al 1995;Miller et al 1998). Most researchers have found a significant tillage effect on poresize distribution as derived from the soil water characteristic, but they found it was dependent on pore-size (Hill et al 1985), depth (Hermawan and Cameron 1993), soil type (Hill 1990), time of sampling (Carter 1988) and crop rotation (Benjamin 1993).…”
Section: Canadian Journal Of Soil Sciencementioning
confidence: 99%
“…Water potentials of -1.5, -0.6 and -0.3 kPa were applied successively (wetting sequence) to the tension infiltrometer to exclude pores 200, 500 and 1000 µm diameter, respectively. Infiltration measurements were taken at each of the four locations (1-cm depth) within each tillage field as outlined by Miller et al (1998). Unsaturated hydraulic conductivity values were estimated for potentials of -0.3, -0.1, -0.6 and -1.5 kPa using the nonlinear regression method of Logsdon and Jaynes (1993).…”
Section: Tension Infiltrometer Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Depending on cultivation history, climate zone and the soil management, saturated and unsaturated hydraulic conductivity under no-till or minimum tillage can be either greater (Benjamin, 1993) or lower (Lindstrom and Onstad, 1984;Heard et al, 1988;Miller et al, 1998) than that under continuously tilled treatments, or not significantly different from that under continuously tilled treatments (Belvins et al, 1983;Obi and Nnabude, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Tillage loosened the soil of the plough layer, and this led to a reduction in bulk density and a rise in total porosity of the plough layer (Table 2). Since tillage increased soil unsaturated hydraulic conductivity (Kargas and Londra, 2015;Miller et al, 1998), lower soil volumetric water content was observed under the T treatment. Corresponding to lower volumetric water content of shallow soils, tillage increased the soil air-filled porosity at depths of 2.5 cm and 12.5 cm (Fig.…”
Section: Resultsmentioning
confidence: 94%